A 30-year trend of dairy consumption and its determinants among income groups in Iranian households - Roustaee, Roshanak; Eini-Zinab, Hassan; Ghodsi, Delaram; Mehrparvar Hosseini, Elham; Omidvar, Nasrin; Hosseini, Hedayat; Hosseini Mousavi, Seyed Omid; Rafiee, Hamed (Frontiers in Public Health, 2024)
Milk and dairy products provide essential nutrients and have the potential to prevent chronic diseases, thus reducing healthcare costs. However, there is a lack of consistent and updated data on dairy consumption trends in Iran. This study aims to analyze the trends in dairy consumption among Iranian households from 1991 to 2021, focusing on household-level determinants across different expense groups . The study uses data from the Iranian Household Expenditure and Income Survey conducted annually from 1991 to 2021 to analyze households' dairy consumption. The data includes values and expenses of food and non-food items purchased in the previous month, as well as demographic characteristics of household members. The households were categorized into 10 deciles based on their gross expense. The econometric model used weighted mean per capita milk, yogurt, cheese, and total dairy consumption based on milk equivalent for each decile. The model takes into account changes in income, prices, household composition, education level, occupation, and residency area using panel data. Data preparation and model estimation were performed using RStudio and STATA17 software. Based on the findings, in 1991, per capita milk, yogurt, and cheese consumption were 26.77 kg, 16.63 kg, and 2.42 kg, respectively. By 2021, these figures changed to 22.68 kg, 11.06 kg, and 3.79 kg, reflecting a decrease in milk and yogurt consumption but an increase in cheese consumption. Family size was positively correlated with yogurt